Crusade for social justice P.S Krishnan: bending governance towards the deprived - Devi, V. Vasanthi (Chennai South Vision Books, 2017)
The book is an invaluable compendium for all those who believe in justice, human rights, the vision of the Indian constitution and material and social progress of all Indians. It does not stop with laying down the ideal, but shows how to take on the structure of a caste-class society and the Governments that safeguard the unjust structure, all be it, working from within the system. Students and teachers of issues of deprivation, exclusion and policies for inclusion would specially benefit from it. The book must be a prescribed text for trainees of India$1 (Bs civil and other services, including the judicial service.s
Keywords: Social Justice; Human Right